Menstrual poverty in the context of education and environmental sustainability = Ubóstwo menstruacyjne w kontekście edukacji i zrównoważonego rozwoju środowiska - Keglević, Marta; Lepeduš, Hrvoje; Dremel, Anita (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Often considered a universal symbol of femininity, menstruation Marks a significant rite of passage in a girl`s life. The menstrual experience varies and depends on geographical, cultural, and socioeconomic contexts, which influences perceptions and attitudes toward this phenomenon. Menstrual poverty refers to the inability to ensure basic menstrual hygiene due to shame, lack of education, or financial resources.
Keywords: menstruacja; ubóstwo menstruacyjne; środki higieny menstruacyjnej; edukacja; zrównoważony rozwój; menstruation; menstrual poverty; menstrual hygiene products; education; sustainability